The third Person Full Pronoun in the ‘Pretuguês’ Ninetheenth Century (Revista de Estudos da Linguagem, 2024)
The present work aims to map the behavior of the third person full pronoun, through its syntactic distribution and its referential relations, through its lexical-semantic readings, starting from the φ-feature theory (CARVALHO , 2008, 2017; CERQUEIRA, 2015, 2019, 2020b; HARBOUR; ADGER; BÉJAR, 2008), in minutes produced in 19th century Salvador (OLIVEIRA, 2006), in order to verify which characteristics of this phenomenon were already manifested in this modality of 19th century Brazilian Portuguese. Therefore, in order to understand the pronoun as a decomposable element, the research is guided by the generativist perspective (CHOMSKY, 1995 and later), whose guidelines guide the selected linguistic variables: syntactic position of the pronoun, readings of definiteness, specificity and animacy, in addition to gender and number. As for the socio-historical framework, the quantitative method enabled the verification of ways to understand the portrait of the full third-person variant, in the linguistic community in question (LABOV, 1972). Therefore, it was found that the third person full pronoun in nineteenth-century Soteropolitan Pretuguese is favored in subject position (59.78%), although it already occurred in the direct object position (2.11%) and in the prepositional object (8,98%). This pronoun tends to present a defined reading (94.7%), specific (98.94%) and animated (75.13%). It also occurs more frequently as masculine (81.48%) and singular (90.57%), aspects strongly linked to the textual genre minute, as well as to the profile of the community in question.